2010
DOI: 10.1097/inf.0b013e3181eb7388
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Screening for Cytomegalovirus Infection in Pregnant Women in Cuba as Prognostic Markers of Congenital Infection in Newborns

Abstract: Mothers with active infection during the pregnancy and with HCMV excretion had significant risks, RR = 1.16 and RR = 1.35, respectively, to have congenitally infected children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Many laboratories using CMV IgG avidity to discriminate primary from nonprimary CMV infection follow a reflexive algorithm whereby only CMV IgG-positive samples that are also CMV IgM positive are tested for CMV IgG avidity (6,17,18,31,34,48,58); yet, investigators that have tested all CMV IgG-positive samples for avidity, regardless of the CMV IgM result, have consistently found that 1% to 3% of IgG-positive, IgMnegative samples exhibit low IgG avidity (16,48,57), suggesting an increased risk of intrauterine transmission. Indeed, transmission has been documented in patients who lacked CMV IgM but exhibited low IgG avidity (14,61); it is likely that these women were in the narrow time window when IgM reversion has occurred but avidity is still low (3,(28)(29)(30)(31).…”
Section: How Should Intermediate CMV Igg Avidity Results Be Used?mentioning
confidence: 99%
See 3 more Smart Citations
“…Many laboratories using CMV IgG avidity to discriminate primary from nonprimary CMV infection follow a reflexive algorithm whereby only CMV IgG-positive samples that are also CMV IgM positive are tested for CMV IgG avidity (6,17,18,31,34,48,58); yet, investigators that have tested all CMV IgG-positive samples for avidity, regardless of the CMV IgM result, have consistently found that 1% to 3% of IgG-positive, IgMnegative samples exhibit low IgG avidity (16,48,57), suggesting an increased risk of intrauterine transmission. Indeed, transmission has been documented in patients who lacked CMV IgM but exhibited low IgG avidity (14,61); it is likely that these women were in the narrow time window when IgM reversion has occurred but avidity is still low (3,(28)(29)(30)(31).…”
Section: How Should Intermediate CMV Igg Avidity Results Be Used?mentioning
confidence: 99%
“…The other 3 groups modified a CMV IgG kit to include a urea buffer wash step; the Brussels and Paris groups employed 8 M urea, whereas the Stuttgart group used 6 M urea. Other investigators have taken the latter approach of modifying CMV IgG kits from different manufacturers and typically employ 6 M urea (16,17,20,22,41,42). Table 2 lists the currently available CMV IgG avidity assays known to the authors.…”
Section: Commercially Available CMV Igg Avidity Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…In this population, CMV acquisition occurs at a rate of 1 to 7% per year (31) and usually follows frequent and prolonged contact with young children (less than 3 years of age) (31)(32)(33)(34). By comparison, in resource-poor communities in industrialized countries and in developing countries, CMV is usually acquired very early in life owing to breast milk transmission and crowded living conditions, and far fewer adult women are seronegative (7,(35)(36)(37)(38)(39)(40)(41).…”
Section: Epidemiology and Clinical Outcomesmentioning
confidence: 99%